Initial clinical evidence on biperiden as antiepileptogenic after traumatic brain injury—a randomized clinical trial - Foresti, Maira Licia; Garzon, Eliana; de Moraes, Mariana Teichner; Valeriano, Rafael P. S.; Santiago, João Paulo; dos Santos, Gustavo Mercenas; Longo, Natália Mata; Baise, Carla; Andrade, Joaquina C. Q. F.; Susemihl, Maria Alice; Leite, Claudia da Costa; Naffah Mazzacoratti, Maria da Graça; et al. (Frontiers in Neurology, 2024)
There is currently no efficacious intervention for preventing post-traumatic epilepsy (PTE). Preclinical studies support the potential use of anticholinergics for this condition. The purpose of this study was to evaluate the effects of biperiden as an intervention for preventing PTE. A randomized, double-blinded clinical trial was conducted at HC/FMUSP between 2018–2022. Adults with acute traumatic brain injury (TBI) were randomly assigned to receive biperiden or placebo, for 10 days. The primary outcome was the incidence of PTE while the secondary outcomes included the frequency of seizures, the frequency of any adverse events and mortality after 24 months. The study was powered at a planned enrolment of 132 patients. The trial began in January 2018 and was halted by researchers on March 2020 (and terminated in December 2022) in the face of the global COVID-19 pandemic. Overall, 123 participants were randomized and 112 contributed with data for modified mITT analysis, being that 61 (49.5%) participants completed the 24-month follow-up consult. Data analysis indicated lack of evidence of biperiden for either, the incidence of post-traumatic epilepsy (2.6, 95%CI, 0.65–10.57; p = 0.170) or the mortality rate (1.57, 95%CI, 0.73–3.38; p = 0.248). The frequency of late post-traumatic seizures was higher for biperiden group (2.03, 95%CI = 0.912–3.1597; p <0.001). The present study suggests that there was insufficient evidence regarding the effect of biperiden in preventing PTE after TBI, which underpins the need for larger studies. Clinical trial registration: ClinicalTrials.gov, identifier: NCT01048138.